THE EFFECT OF CEO NARCISSISM, COMPANY SIZE, BOARD OF DIRECTORS SIZE AND BOARD OF COMMISSIONERS SIZE ON COMPANY VALUE IN THE COVID-19 PANDEMIC WITH CAPITAL STRUCTURE AS CONTROL VARIABLE AND FINANCIAL PERFORMANCE AS INTERVENING VARIABLE - Bambang Sugiharto; Muhammad Syeh Dinar; Trisandi Eka Putri (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
This study aims to analyze how the effect of CEO narcissism, company size, board size, and board of commissioners size on firm value in the covid-19 pandemic with capital structure as a control variable and financial performance as an intervening variable in manufacturing companies in Southeast Asia. The population used in this study are manufacturing companies in Southeast Asia, totaling 736 companies. The sampling technique used is using the Slovin formula. Based on the Slovin formula, a sample of 193 companies was obtained. The analytical method used in this research is multiple regression analysis. The results showed that CEO narcissism and board size had a positive effect on firm value, board size had no effect on firm value, while firm size had a negative effect on firm value. Then indirectly the CEO narcissism, the size of the board of directors, and the size of the board of commissioners through financial performance have no effect on firm value, while the size of the company indirectly through financial performance has an effect on firm value.